Efektivitas Pembelajaran Berbasis Literasi Digital Dan Literasi Membaca Terhadap Pemahaman Konsep Siswa Dalam Mata Pelajaran IPS Kelas IX SMP - Nailariza Umami; Elifta Dwi Febriati; Imam Sukwatus Suja’i (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
Concept understanding is an essential competency in Social Studies learning that supports students in comprehending and applying learning materials. However, preliminary observations at SMP Negeri 3 Pagerwojo revealed that students’ conceptual understanding remained low. This study aimed to analyze the effects of digital literacy-based learning and reading literacy-based learning on students’ conceptual understanding and to compare the effectiveness of both approaches. The research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of two classes: Class IX A received digital literacy-based learning, while Class IX B received reading literacy-based learning. Data were collected through pretests and posttests measuring students’ conceptual understanding. The data were analyzed using validity, reliability, normality, homogeneity, Independent Sample t-test and N-Gain analyses. The findings indicated that both digital literacy-based learning and reading literacy-based learning significantly affected students’ conceptual understanding. The average posttest score of the digital literacy class was 79.52, while that of the reading literacy class was 85.81. The hypothesis test showed a significance value of 0.000 (<0.05), indicating a significant difference between the two learning approaches. Reading literacy-based learning was found to be more effective than digital literacy-based learning in improving students’ conceptual understanding in Social Studie.